Regression analysis of experimental data for added resistance in waves of arbitrary heading - Sushanth, Shreya (Nanyang Technological University, 2024)
With the current worldwide rules focusing on energy economy and emissions control in marine operations, there is a growing worry about additional resistance in ships travelling in waves. This research aims to solve this issue. The economic and environmental performance of a ship is greatly impacted by increased resistance, especially in low- to moderate-sea states. Not only does it impact speed and power in harsher seas, but it also has an impact on navigational safety, particularly for underpowered boats like tankers and bulk carriers. There has been a trend towards semi-empirical approaches due to the difficulties traditional methods have in estimating additional resistance, particularly in low sea states with shorter waves. Because of nonlinear motion events, the complexity rises at higher sea states. Advances in numerical technologies, such Computational Fluid Dynamics, have been limited by recent investigations indicating a need for further development. Therefore, the objective of the study is to make a contribution to this subject by improving the precision and dependability of additional resistance forecasts under different sea conditions. More emphasis will be given to creating an extensive experimental database in order to do this, since it is essential for verifying and improving both sophisticated numerical simulations and more basic empirical models. Inherently difficult to measure additional resistance will be addressed by the research, including errors from small measured amounts and incident wave quality in experimental settings. Furthermore, the research will tackle pragmatic concerns including diverse methodologies for measurement, dimensions of models, and the consequences of executing experiments in diverse settings. The scale effect on additional resistance tests will also be investigated, especially in cases where viscosity is an important factor. Thus, the project's goal is to produce more precise and dependable data for both regular waves by addressing these elements. This will aid in the creation of more advanced prediction tools for enhanced resistance in ship design and operation.